Workload, social support and emotional stability - Huth, Andreas (Naše gospodarstvo, 2025)
The following article examines the question of whether factors such as workload and social support from colleagues and superiors have a significant positive or negative impact on the emotional well-being of employees. Additionally, it compares the results between Croatia and Germany in the context of the COVID-19 pandemic. For this purpose, a sample of 1,800 employees (900 per country) was used for statistical analysis, using data from the European Working Conditions Telephonic Survey. A descriptive analysis and an inferential analysis using the nonparametric Mann-Whitney U test were performed for variables such as work-life balance, high-speed work, work under time pressure, work autonomy, perceived well-being, disruptive emotions, presenteeism, and social support from colleagues and supervisors. The results show that Croatians exhibit a higher level of emotional stability than German employees, as they tend to be happier and in a better mood, have a lower workload, and receive more social support from coworkers and managers.
Keywords: Croatian; čustvena stabilnost; delovna obremenitev; emotional stability; German; Hrvaška; Nemčija; social support; socialna podpora; workload